Splenic abscess leading to spontaneous splenic rupture - Annum A. Bhullar (Emergency Care Journal, 2021)
Spontaneous, atraumatic rupture of the spleen is an uncommon but potentially fatal cause of acute abdominal pain. Splenic abscesses are equally rare and can be a risk factor for spontaneous splenic rupture. We present a 45-year-old man with no past medical or surgical history who presented with acute worsening of left upper abdominal pain that had been present for months, who was discovered to have a ruptured spleen. Splenic abscess was discovered intra-operatively and was thought to have developed after dental work. Recognizing presenting features of spontaneous splenic rupture and understanding its potential causes, such as splenic abscesses, may prevent delayed or missed diagnosis and guide treatment, which typically includes emergent splenectomy.